Empowering Organizational Performance through Budgeting Dynamics in Indonesia: Memberdayakan Kinerja Organisasi melalui Dinamika Penganggaran di Indonesia - Pribadi, Moch Ayub Johan; Biduri, Sarwendah (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative study investigates the impact of budget preparation participation and budget target clarity on the performance of regional apparatus organizations (OPDs) in Sidoarjo Regency, Indonesia, with organizational commitment as a moderating variable. Utilizing SmartPLS version 3.0, data was collected from 78 respondents across 26 OPDs using purposive sampling. Findings reveal that both budget preparation participation and budget target clarity significantly influence OPD performance, while organizational commitment moderates the effect of budget target clarity but not budget preparation participation. The study underscores the importance of active participation in budgeting processes and clear budget targets in enhancing OPD performance, offering valuable insights for policymakers and organizational leaders aiming to optimize budgeting practices and bolster organizational effectiveness. Highlights: Budget involvement enhances OPD performance. Organizational commitment moderates budget clarity's effect. Findings inform policy for optimizing organizational effectiveness. Keywords: Budgeting, Organizational Commitment, OPD Performance, SmartPLS, Sidoarjo Regency.